Image of Pericles in Vladislav Buzeskul’s Works and German Classical Scholarship: Some Notes - Khrustalyov, Vyacheslav (Hyperboreus, 2016)
The author expresses some thoughts concerning the image of Pericles created by a distinguished Russian historian Vladislav Buzeskul (1858–1931) in his works, particularly in his Master’s thesis. Buzeskul’s views of Pericles’ personality and activities are compared with those of some prominent German scholars, such as M. Duncker, K. J. Beloch etc.